Program Project Management of Sponsored Programs in a University Environment. - Ohio State Univ., Columbus. Research Foundation; Ohio State Univ., Columbus. Research Foundation ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
Management is a future-oriented decision process that relates resources into a total functional system for the accomplishment of a set of objectives. As a rule, universities do not have a management system, and there is no understanding of their environments in terms of the inputs, outputs, objectives, and organizational relationships of line and staff necessary for such a system. Hence, many of the problems of project management in the university arise from the lack of integrated planning, programming, and budgeting, and from an operational structure which does not encourage effective collection, distribution, and control over resources. Sponsored projects and programs involve a special set of relationships between the university, the faculty, and the sponsoring agency. These relationships create a unique sector of the university environment in which the individual faculty member is responsible for "selling" his program to a sponsor, and the university is responsible for assuring compliance on the part of the faculty member. The requirements of project management, the needs of a university management system, and the special demands placed on these 2 systems by an outside sponsor call for a separate administrative sub-system geared to meet the specific demands of sponsored programs. Such a system would ensure the proper monitoring of the commitment of university resources and the preservation of the priorities and goals of the operating structure of the university. (WM)
Educational level discussed: Higher Education.
ERIC Note: Paper presented as part of the Management Training Program for Educational Research Leaders, Columbus, Ohio, September 18, 1968.
Sponsoring Agency: Office of Education (DHEW), Washington, DC.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Planning; Higher Education; Systems Development; Administration; Administrative Principles; Institutional Environment; Program Administration; Research Projects